(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Generative Artificial Intelligence (AI) is revolutionizing healthcare with its transformative potential in medical imaging, drug discovery, and clinical decision-making. Generative models such as Generative Adversarial Networks (GANs), Variational Autoencoders (VAEs), and large foundation models can synthesize realistic data, emulate biological systems, and accelerate innovation beyond traditional AI methods. In medical imaging, generative AI enhances diagnostic accuracy by enabling high-resolution image reconstruction, noise reduction, anatomical segmentation, and the creation of synthetic datasets to support algorithm training in data-scarce environments. These advancements assist radiologists in early disease detection, treatment planning, and longitudinal patient monitoring. In drug discovery, generative AI accelerates molecule design, lead optimization, and prediction of protein-ligand interactions, reducing time and cost while enabling precision therapeutics and drug repurposing. Clinically, it supports automated report generation, patient-specific treatment simulations, and digital twin development for disease modeling and trial optimization through synthetic patient cohorts. Despite these advances, challenges persist regarding data quality, interpretability, regulatory approval, ethical transparency, and bias mitigation, which are critical for ensuring patient trust and safety. This study explores generative AI’s applications across medical imaging, pharmacology, and clinical workflows, highlighting its opportunities, limitations, and future directions toward sustainable, ethical, and patient-centered healthcare integration.